2017
DOI: 10.20856/jnicec.3808
|View full text |Cite
|
Sign up to set email alerts
|

Disney strategy for Japanese university students' career guidance: A mixed methods pilot study

Abstract: The Disney strategy, a neuro-linguistic programming skill, has been reported to be useful for career guidance by qualified career consultants in Japan. This mixed methods pilot study aimed to examine the effects and the experience of using this strategy for career guidance in Japanese students. Six students responded to four job-search-related scales at pre-training and post-training, and were interviewed. Students' self-esteem and job-search self-efficacy increased significantly in the short-term. Thematic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…These relationships have not previously been explored in this student group and the study findings indicate that it would be worthwhile to formulate and/or evaluate interventions aimed at cultivating intrinsic motivation in business students. An example of such an intervention might be the Disney strategy -modelled from how Walt Disney achieved his dreams, accessing the dreamer, realist, and critique position with a certain cognitive mode and body movement (Dilts, 1998) -that has been shown to help other student groups identify with their inner passion and augment intrinsic motivation (Kotera & Sheffield, 2017).…”
Section: Discussion and Recommendations For Additional Researchmentioning
confidence: 99%
“…These relationships have not previously been explored in this student group and the study findings indicate that it would be worthwhile to formulate and/or evaluate interventions aimed at cultivating intrinsic motivation in business students. An example of such an intervention might be the Disney strategy -modelled from how Walt Disney achieved his dreams, accessing the dreamer, realist, and critique position with a certain cognitive mode and body movement (Dilts, 1998) -that has been shown to help other student groups identify with their inner passion and augment intrinsic motivation (Kotera & Sheffield, 2017).…”
Section: Discussion and Recommendations For Additional Researchmentioning
confidence: 99%
“…An example of such a dual-purpose career planning technique is the Disney strategy that seeks to develop specific cognitive competencies based on how Walt Disney realised his dreams (Dilts 1995). The Disney strategy is reported as being a useful career guidance approach that has not only helped students foster a clearer future vision but also foster positive emotions, contributing to better mental health (Kotera 2018;Kotera and Sheffield 2017). This type of practical career exercise could be embedded in the business education curriculum without excessive training or logistical demands on education providers.…”
Section: Discussionmentioning
confidence: 99%
“…The Disney strategy, modeled from how Walt Disney realized his dreams, guides employees to access cognitive and physiological styles of a dreamer, realist, and critique (Dilts, ). Among career‐focused university students, this strategy enhanced their self‐efficacy, and their interviews implied relevance to the other PsyCap constructs (Kotera & Sheffield, ). Future HRD research using controlled study designs is thus warranted to assess the effects of such NLP techniques on workers' PsyCap (controlled designs are emphasized because they would maximize methodological rigor and therefore reduce “Pollyannaish fluff” [Luthans, , p. 4] that has been highlighted as an issue within the field of organizational positive psychology [Luthans, ]).…”
Section: Discussionmentioning
confidence: 99%
“…Among the NLP skills used in the included studies, skills that helped employees to have a vision for the future seemed particularly useful (HemmatiMaslakpak et al, ; Hollander & Malinowski, ; Thompson et al, ). Using the Disney strategy, Kotera and Sheffield () reported that creating a clear vision for the future was particularly useful to participants' professional career planning. Given that workers are often preoccupied and overwhelmed with the tasks they have to perform, NLP skills aimed at formulating a clear and attractive future goal can help provide a sense of purpose in life (Kotera et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation